2010
DOI: 10.1063/1.3457155
|View full text |Cite
|
Sign up to set email alerts
|

Fivefold differential cross sections for ground-state ionization of aligned H2 by electron impact

Abstract: We discuss the ionization of aligned hydrogen molecules into their ionic ground state by 200 eV electrons. Using a reaction microscope, the complete electron scattering kinematics is imaged over a large solid angle. Simultaneously, the molecular alignment is derived from postcollision dissociation of the residual ion. It is found that the ionization cross section is maximized for small angles between the internuclear axis and the momentum transfer. Fivefold differential cross sections (5DCSs) reveal subtle dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
(34 reference statements)
0
42
1
Order By: Relevance
“…For the initial state of the above model the Coulomb interaction between the projectile and the screened nuclear charge for a neutral target is contained to all orders of perturbation theory while the initial-state non spherical projectile-active-electron interaction is the first order interaction. Senftleben et al [23,28] have reported that M3DW reproduces most of the experimental results, although discrepancies remain. They have also mentioned that 3C-He failed to reproduce experimental FDCS at the ejection energy of (3.5±2.5) eV and the scattering angle of (16±4) o .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…For the initial state of the above model the Coulomb interaction between the projectile and the screened nuclear charge for a neutral target is contained to all orders of perturbation theory while the initial-state non spherical projectile-active-electron interaction is the first order interaction. Senftleben et al [23,28] have reported that M3DW reproduces most of the experimental results, although discrepancies remain. They have also mentioned that 3C-He failed to reproduce experimental FDCS at the ejection energy of (3.5±2.5) eV and the scattering angle of (16±4) o .…”
Section: Introductionmentioning
confidence: 83%
“…Very recently, 5DCS for 200 eV electron impact ionization of hydrogen molecule has been explored experimentally as a function of molecular alignment by Senftleben et al [23,28]. They derived the alignment of the internuclear axis from the fragmentation of the residual H + 2 ion which was produced as a result of the ionizing collision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Till date, a number of theoretical and experimental investigations have been carried out using photons, 1-5 electrons, [6][7][8] and heavy ions [9][10][11][12] as probes to understand the breakup dynamics of molecules including, large biomolecules [13][14][15][16] or even free fullerene. [17][18][19][20][21] To tackle the complexity involved in the molecular break-up processes, it is necessary to have sophisticated, state-of-the-art, theoretical models and highly differential experimental measurements.…”
Section: Introductionmentioning
confidence: 99%